2009
DOI: 10.3945/ajcn.2008.26465
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient profiles discriminate between foods according to their contribution to nutritionally adequate diets: a validation study using linear programming and the SAIN,LIM system

Abstract: On the basis of a few key nutrients, it is possible to predict the ability of a given food to facilitate -- or to impair -- the fulfillment of a large number of nutrient recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
143
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 24 publications
0
143
0
3
Order By: Relevance
“…In addition to technological indexes, nutritional profiling systems could also help classify processed food and discriminate between nutrient-dense and -poor products (58,61). For example, a previous study demonstrated the interest in using a nutritional profiling system to evaluate the processes used for different fruits and meat products; the nutritional SAIN-LIM scores were calculated during processing and very distinctly discriminated between different technologies, including formulation (candying and salting), and other processes (55).…”
Section: Figurementioning
confidence: 99%
“…In addition to technological indexes, nutritional profiling systems could also help classify processed food and discriminate between nutrient-dense and -poor products (58,61). For example, a previous study demonstrated the interest in using a nutritional profiling system to evaluate the processes used for different fruits and meat products; the nutritional SAIN-LIM scores were calculated during processing and very distinctly discriminated between different technologies, including formulation (candying and salting), and other processes (55).…”
Section: Figurementioning
confidence: 99%
“…Indeed, Darmon, et al [20], categorized foods based on their nutrient profiles and yogurt was included in the "Class 1" category, referring to the healthiest food choices alongside with fruits and vegetable. As we previously reported [8], yogurt (all types, independently of their fat content) is a contributor to the Prudent dietary pattern altogether with vegetables, fruits, nuts, non-hydrogenated fats, legumes, fish and other seafood.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional quality: SAIN,LIM and UK Ofcom nutrient profiling models To assess the nutritional quality of each food, two nutrient profiling models were used: the French SAIN,LIM and the UK Ofcom, both precisely described elsewhere (44,45) .…”
Section: Food Pricesmentioning
confidence: 99%